KEEFEKTIFAN PEMBELAJARAN MATEMATIKA DENGAN STRATEGI TEAMS GAMES AND TOURNAMENT (TGT) BERBANTUAN CD INTERAKTIF MATERI PRISMA DAN LIMAS (Pawiyatan, 2015)
The use of inappropriate learning method can make the students feel tired to participate in learning and lead to the lack of the effectiveness of learning development inside classroom. Teams Games and Tournament (TGT) is one of cooperative learning method using game. Using this method, the learning activities between learners can be a fair competition, where they compete to present something they have learnt from Interactive CD. This study aims to determine the effectiveness of mathemathic teaching material and Pyramid prism by Interactive CD-assisted TGT strategy. The effectiveness achieved is characterized by (1) the average achievement of students who learned in experimental class reachede 80,0 ,(2) the average of motivation to learn reach the exhaustiveness of learning motivation, (3) having a positive effect on the motivation of learning achievement, and (4) the students achievement of experimental class is better that control class. The population of this study is the students of SMP N 2 Rembang grade VIII. Using the random cluster sampling technique, it is determined that VIII-2 as experimental group and VIII-3 as control group. The result shows that the average achievement of learners who are taught using Interactive CD-assisted TGT strategy reach 81,35. The average of learning motivation reach to the exhaustiveness of leaning motivation with the value 76.76 from regression calculation, the regression of the estimation of equation is gained between X and Y that is Y= 36.391 + 0.586X with determination coefisien of 49.0%, meaning that there is positive effect on the achievement of learning motivation. In addition, the average ofstudents achievement of experimental group and control class are 77.96 and 81.35. It means that the average of students achiement who learn in the experimental group is better than those who learn in control class. Based on this result, we can draw conslusion that four effective learning are achieved.Keywords: Effectiveness, TGT, Interactive CD, Learning Achievement, Motivation.